TRAFFIC ACCIDENT–RELATED OPEN GLOBE INJURIES. Issue 4 (April 2019) - Okamoto, Yoshifumi; Morikawa, Shohei; Okamoto, Fumiki; Mitamura, Yoshinori; Ishikawa, Hiroto; Ueda, Tetsuo; Sakamoto, Taiji; Sugitani, Kazuhiko; Sawada, Osamu; Mori, Junya; Takamura, Yoshihiro; Oshika, Tetsuro
Abstract : Purpose: To evaluate the clinical characteristics and visual outcomes of patients with traffic accident-related open globe injuries, and to examine preoperative factors influencing the visual prognosis after pars plana vitrectomy, as compared with common open globe injuries. Methods: Patients with open globe injuries, who underwent pars plana vitrectomy, were identified. Patients' demographic and clinical data were entered into a computerized database for review and analysis; data included age, sex, initial visual acuity, duration between onset of injury and surgery, information about the type and cause of injury, wound location and length, presence of ocular complications, and final visual acuity. Results: Of the 355 open globe injuries, 14 were sustained during a traffic-related accident; the average age was 50.4 years (range: 20–85) and most (78.6%) were men. Of these 14 patients, 9 (64.3%) presented with rupture and 5 (35.7%) with laceration. Injuries were caused while driving (6 eyes; 42.9%), riding a bicycle (5 eyes; 35.7%), involved in car accident while walking (2 eyes; 14.3%), and riding a motorbike (1 eye; 7.1%). Initial visual acuity was significantly related to final visual acuity ( P = 0.003, R 2 = 0.80). The final visual acuity in patients with traffic accident–related open globe injuries was significantly better than that of the total group ( P = 0.01). Conclusion: Traffic accident–related open globe injuries had better visual outcomes than common open globe injuries. Visual outcomes in patients with traffic accident–related open globe injuries were related to the initial visual acuity. No eyes developed endophthalmitis in patients with traffic accident–related open globe injuries. Abstract : The authors investigated the clinical characteristics and visual outcomes of patients with traffic accident–related open globe injuries. Traffic accident–related open globe injuries had better visual outcomes than common open globe injuries. Visual outcomes in patients with traffic accident–related open globe injuries were related to the initial visual acuity.